Job Differentiation and Wages - Stokey, Nancy L. (Quarterly Journal of Economics, 1980)
The determination of wage rates and skill requirements for jobs is studied in a model where workers, who vary in ability, acquire skill through (costly) training. If firms' skill requirements are fixed, there exists a unique Nash equilibrium in wage rates, but the resulting allocation of labor is inefficient. The Nash equilibrium wage rates and allocation of labor approach the competitive equilibrium if and only if the number of job types increases on every skill range and no firm remains a monopsonist on any skill range. If firms choose both skill requirements and wage rates, no Nash equilibrium in pure strategies exists.